Gasto público en educación, salud y nutrición de niños, niñas y adolescentes en el Perú (2000–2005) - Muñoz, Ismael (2007)
The evolution of fiscal spending in nutrition, health and education of children and adolescents between 2000–2005, has not been following the same pattern of growth as that of GDP in the same period of time in Peru. These important components of public policy in childhood and adolescence have not been properly attended with the larger resources collected by the State, specially in the nutrition area given that fiscal real expenditure in that area fell in spite of the rapid growth of GDP during the period of our study. With the figures found in the SIAF, the structure of publicexpenditure in the indicated components has been constructed, according to the expenditure budgetary functions, allowing us to establish a base that allows us to make proposals on improvements in public policy in the formation of the human capital since childhood.